A grande transformação : a formação sacerdotal da Arquidiocese de São Paulo (1958-1984) - Santa Bárbara Júnior, Camilo Antônio (2014)
This thesis examines the changes in priestly formation at the Archdiocese of São Paulo between 1958 and 1984, focusing on the following dimensions: working method, disciplinary measures, spiritual practices and intellectual formation. Although the changes are concerned with the nature of social institutions, this period was characterized by very intense changes in priestly formation towards an increasing secularization of the religious practices and discourse. This thesis, based on the theoretical tools developed by the sociologist Peter Berger, examines the correlations between the modernization of São Paulo society, with its consequent objective and subjective secularization process, and changes occurred in the archdiocesan priestly formation. Therefore, as Brazil and the city of São Paulo - advanced center of Brazilian modernization - were introduced in the spiral process of rapid secularization, traditional Catholic education has become dysfunctional to the interests of Catholicism. After all, to each form of social organization corresponded certain kind of Catholic priest whose function was to conserve or enhance the structure of domination of Catholicism. For this, it was necessary to strengthen its plausibility structure, namely, the social base that makes it a socially relevant discourse. Within the context of the military regime and the opening of the Catholic Church to the world, with the ecclesiastical politics of Vatican II, d. Paulo Arns decided to put the archdiocese in the struggle for human rights and criticism of the Brazilian development model. Thus, opted to introduce archdiocesan Catholicism into the interests and secular reality, considering that the secularized religious clientage of São Paulo has secular issues at the center of their interests. For this, had to operate a reordering of archdiocesan pastoral, including priestly formation in order to adapt it to new pastoral praxis. This process of secularization of religious consciousness led to the end of educational activity at the seminary and the reform of theology school in accordance with the canons of secular thought. Therefore, emerged a new kind of priestly formation and a new secularized religious discourse that legitimated it: liberation theology.